2022
DOI: 10.2147/ceor.s341896
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of High-Risk Non-Muscle Invasive Bladder Cancer (HR-NMIBC) in Real-World Evidence (RWE) Studies: Systematic Literature Review (SLR)

Abstract: Background: To date, there has been limited synthesis of RWE studies in high-risk nonmuscle invasive bladder cancer (HR-NMIBC). The objective of this research was to conduct a systematic review of published real-world evidence to better understand the real-world burden and treatment patterns in HR-NMIBC. Methods: An SLR was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with the scope defined by the Population, Intervention Comparators, Outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Of the 1,049 BC patients who received BCG from our cohort, 11% showed recurrence during the study period, as de ned according to intravesical dispensation of mitomycin, epirubicin, gemcitabine or doxorubicin. A recent SLR described ve-year recurrence-free survival in high-risk NMIBC patients to range from 17-89%, highlighting important variations across RWE studies (19). Another recent study has estimated a 5-year recurrence rate ranging between 56 and 77%, depending on disease grade (20).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 1,049 BC patients who received BCG from our cohort, 11% showed recurrence during the study period, as de ned according to intravesical dispensation of mitomycin, epirubicin, gemcitabine or doxorubicin. A recent SLR described ve-year recurrence-free survival in high-risk NMIBC patients to range from 17-89%, highlighting important variations across RWE studies (19). Another recent study has estimated a 5-year recurrence rate ranging between 56 and 77%, depending on disease grade (20).…”
Section: Discussionmentioning
confidence: 99%
“…CSS and OS were significantly shorter in BCG‐unresponsive patients compared to non‐BCG‐unresponsive patients with 5‐year CSS (90.6% vs. 97.3%, p < 0.0001) and 5‐year OS (82.9% vs. 92.4%, p < 0.0001). In addition, a larger systematic literature review of 160 studies reporting high‐risk NMIBC from the USA, Europe, Canada, and Australia demonstrated that the 5‐year CSS rate of BCG‐unresponsive disease treated with intravesical therapy was only 71% 79 …”
Section: Advancements In Treatment Strategy For Bcg‐treated Nmibcmentioning
confidence: 99%
“…The EORTC risk table 51 The CUETO risk table 52 The J-NICE risk table 61 The TMDU risk table 63 BCG-unresponsive disease treated with intravesical therapy was only 71%. 79 Although a few reports have been published, real-world evidence from Japan is limited. Our previous single-center retrospective study showed that 49 (30%) out of 165 patients treated with BCG developed BCG-failure disease, and BCG-unresponsive disease (n = 18) was associated significantly with a high risk of progression compared with non-BCG-unresponsive disease (n = 31, p = 0.03).…”
Section: Factormentioning
confidence: 99%
“…The main treatment for high-risk nonmuscle invasive bladder cancer (HR-NMIBC; T1, high-grade Ta and/or carcinoma in situ) is transurethral resection of bladder tumour followed by bacillus Calmette-Guérin (BCG) bladder-perfusion therapy. 53 However, only 50% of patients benefit from BCG. 54 In response to the dilemma of some patients not of UC specimens.…”
Section: Role Of Cpis In High-risk Nonmuscle Invasive Bladder Cancermentioning
confidence: 99%